ARTICLE THE CORRELATION BETWEEN WORK-LIFE BALANCE AND JOB SATISFACTION AMONG GEN-Z EMPLOYEES - Angelika Agata Pinses; Menik Tetha Agustina (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
This study aims to examine the relationship between work-life balance and job satisfaction among Generation Z employees. This research employed a quantitative approach using a correlational method. The participants of this study were Generation Z employees selected through purposive sampling. Data were collected using Likert-scale questionnaires measuring work-life balance and job satisfaction. The data were analyzed using Pearson correlation analysis. The results showed a correlation coefficient of 0.546 with a significance value of 0.000 (p < 0.05), indicating a positive and significant relationship between work–life balance and job satisfaction. This finding suggests that better work–life balance is associated with higher job satisfaction among Generation Z employees.